1Discounting Rate for Nominal and Real Cash Flow in the Assessment of its Current Value - Guli Yarkinovna Mukhibova (Zien Journals, 2023)
The calculation of the discount rate is a necessary step in assessing the market value of objects of appraisal, as well as the effectiveness of investment projects. The article outlines specific methods for assessing the discount rate when analyzing cash flows and the effectiveness of investment projects in the context of inflation. The relationship between the nominal rate of return used as the discount rate and the effect of inflation on the volume of cash flows is stated. Recommendations are given on the use of nominal and real rates of return in the calculation of cash flows, both in current and in basic prices
Keywords: Assessment object; investment project; nominal and real rate of return